Treating protracted corneal ulcers with UVA corneal collagen crosslinking: clinical cases - E. V. Yani; E. N. Iomdina; V. V. Pozdniakova; V. A. Golikova; K. E. Seliverstova (Российский офтальмологический журнал)
It has recently been proposed to use ultraviolet (UVA) corneal collagen crosslinking as an alternative method of treating bacterial ulcerative lesions of the cornea. Ambivalent results regarding the efficacy and safety of this method of treatment limit its implementation in clinical practice so far.The purpose of this work is to analyze three clinical cases involving the use of a new device for local UVA crosslinking in the complex treatment of bacterial corneal protracted-course ulcers with the suspected development of mixed fungal infection.Material and methods. For a dynamic follow-up of patients, we used biomicroscopy with a fluorescein test, photo registration and optical coherence tomography of the anterior part of the eye. Inflammatory changes were assessed using a point scale.Results. 3–5 procedures of local UVA exposure (with instillations of 0.1% riboflavin solution) lasting 3–5 minutes each and given with an interval of 2–4 days ensured stable and fast epithelialization of the cornea and a significant increase in visual acuity in the inflammatory process outcome.Conclusion. The first results of treating bacterial corneal ulcers using a new portable device for local UVA crosslinking have shown its high therapeutic efficiency and good prospects for further use in clinical practice.